Evaluation of a torque driven computer simulation model of springboard diving - Yeadon, M. R.; Kong, P. W.; King, M. A. (2006)
The use of computer simulation models in studies of human movement is now widespread. Most of these models, however, have not been evaluated in a quantitative manner in order to establish the level of accuracy that may be expected. Without such an evaluation little credence should be given to the results and conclusions drawn. In order that a quantitative comparison can be made between simulation and performance the model should be customised to an individual subject by determining subject-specific parameters. Kinematic data can then be collected on a performance by the subject and the model evaluated by comparing simulation output variables with the corresponding values from the data collection. The aims of this study were to determine subject-specific parameters for input into a torque-driven computer simulation model of springboard diving takeoff and to carry out a kinematic evaluation of the model with a view to using the model to investigate optimum techniques in the forward and reverse dive groups